CRITICAL THINKING AS GROUNDS OF SOCIALLY RESPONSIBLE COMMUNICATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Companies and individuals are willing to introduce the principles of social responsibility in their everyday working practices, still, in order to accomplish this and to have real gains for the company and society, the concept of social responsibility has to be understood in the broadest sense. This understanding is based on critical information processing or critical thinking.  Information can be obtained through reflection, observation, communication, experience, etc. The aim of the research is to study the factors that influence the basic principles of critical thinking formation, which are the basis of socially responsible communication. The authors employ the monographic method for charting the theoretical framework, the survey to research respondent’s’ ability to evaluate information critically and to make socially responsible decisions. As the result of research the authors conclude that development of the critical thinking competences can raise the level of social responsibility on the individual and societal level.